2018
DOI: 10.1038/s41598-018-26558-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-level Brodifacoum Exposure on the Feline Immune Response

Abstract: Anticoagulant rodenticides have been implicated as a potential inciting factor in the development of mange in wild felids, but a causative association between anticoagulant rodenticide exposure and immune suppression has not been established. Specific-pathogen-free domestic cats were exposed to brodifacoum over a 6-week period to determine whether chronic, low-level exposure altered the feline immune response. Cats were vaccinated with irrelevant antigens at different points during the course of the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In the light of our findings, BDF is suggested to be immunosuppressor confirmed by obvious reduction in LYM, EOS and MON count. Nevertheless, BDF exposure did not influence the immune response of cat at the terms of antibody production and lymphocyte proliferation but it was associated with alternations in cytokine expression (Kopanke et al, 2018). This controversy may arise from the difference in experimental design as dose of BDF, species of animal model, and duration of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of our findings, BDF is suggested to be immunosuppressor confirmed by obvious reduction in LYM, EOS and MON count. Nevertheless, BDF exposure did not influence the immune response of cat at the terms of antibody production and lymphocyte proliferation but it was associated with alternations in cytokine expression (Kopanke et al, 2018). This controversy may arise from the difference in experimental design as dose of BDF, species of animal model, and duration of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This controversy may arise from the difference in experimental design as dose of BDF, species of animal model, and duration of exposure. Decreased release of granulocyte monocytes-colony stimulating factor may lie behind the immunosupressor effect of BDF as this factor induces granulocyte and macrophage populations from bone marrow precursor cells and increases regulatory T-cell numbers and function (Bhattacharya et al, 2015a;Bhattacharya et al, 2015b;Kopanke et al, 2018). In addition, suppression of lymph node activity and diapedesis of LYM out of the blood vessels to injured intestine might account for a decrease in LYM number (Mirkov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The speci c levels of individual AR concentrations are di cult to interpret because these values are labile with expected decline after initial exposure and deposition in the liver. Moreover, the half-life of these compounds in shers, and indeed any carnivores, is largely unknown (Kopanke et al, 2018). Likewise, lethal doses have not been determined for shers for any of these compounds and studies of other mustelids have found large disparities even for the most common compound, brodifacoum (Fournier-Chambrillon et al, 2004, Alterio, 1996, Alterio et al, 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suspect that subtoxic levels of ARs might interfere with the immune response by disrupting leukocyte differentiation ( Fraser et al, 2018 ), besides, other work indicates that ARs increase susceptibility to opportunistic infections in bobcats ( Serieys et al, 2018 ). Nevertheless, experiments have shown that cats exposed to brodifacoum showed transient decreases in the production of certain cytokines, without significant impact on the immune response ( Kopanke et al, 2018 ). Other felids such as lynx were found to be at high risk of exposure, with a record of fetal transfer of several ARs.…”
Section: Discussionmentioning
confidence: 99%